2017
DOI: 10.3390/ijms18020436
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Inhibit the Proliferation of Human Umbilical Vein Endothelial Cells by Inhibiting Cathepsin D

Abstract: We aimed to investigate the effect of advanced glycation end products (AGEs) on the proliferation and migration ability of human umbilical vein endothelial cells (HUVECs). Cell proliferation was detected by methyl thiazolyl tetrazolium (MTT) assay, real-time cell analyzer and 5-Ethynyl-2′-deoxyuridine (EdU) staining. Cell migration was detected by wound-healing and transwell assay. AGEs significantly inhibited the proliferation and migration of HUVECs in a time-and dose-dependent way. Western blotting revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Chen et al 32 reported that AGEs increased the ratio of LC3-II/I but had no obvious effect on p62 protein expression in HUVECs. Li et al 33 demonstrated that AGEs dramatically increased the expression of LC3-II/I and p62 in HUVECs. In our study, we observed a similar phenomenon in EPCs, as AGEs increased the ratio of LC3-II to LC3-I, while p62 was also accumulated, suggesting the impairment of autophagic flux rather than the activation of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al 32 reported that AGEs increased the ratio of LC3-II/I but had no obvious effect on p62 protein expression in HUVECs. Li et al 33 demonstrated that AGEs dramatically increased the expression of LC3-II/I and p62 in HUVECs. In our study, we observed a similar phenomenon in EPCs, as AGEs increased the ratio of LC3-II to LC3-I, while p62 was also accumulated, suggesting the impairment of autophagic flux rather than the activation of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar manner, the incorporation of 5-bromo-2′-deoxyuridine (BrdU) or EdU (5-ethynyl-2′deoxyuridine) can be measured. BrdU or EdU can be (in)directly detected and subsequently be (semi-) quantified using ELISA, flow cytometry, or immunohistochemistry [ 57 , 58 , 60 ]. The latter two quantification techniques allow one to determine the fraction of dividing cells.…”
Section: Endothelial Cell Proliferation Assaysmentioning
confidence: 99%
“…For example, the indirect detection of antigens (e.g., PCNA or BrdU) requires careful procedural optimization. Although the alternative “click” chemistry, by which the analogous EdU can be detected directly, circumvents this issue of indirect detection, making EdU preferable [ 57 , 58 , 60 ]. Nonetheless, assay readout and interpretation are important to consider.…”
Section: Endothelial Cell Proliferation Assaysmentioning
confidence: 99%
“…When autophagy is induced, LC3 is converted from the cytoplasmic form LC3-I into the membrane-associated form LC3-II. The ratio of LC3-II/LC3-I is widely considered as a primary marker of autophagy activation ( 40 , 41 ).…”
Section: Resultsmentioning
confidence: 99%